Music and social bonding: “self-other” merging and neurohormonal mechanisms - Tarr, Bronwyn; Launay, Jacques; Dunbar, Robin I. M. (Frontiers in Psychology, 2014)
It has been suggested that a key function of music during its development and spread amongst human populations was its capacity to create and strengthen social bonds amongst interacting group members. However, the mechanisms by which this occurs have not been fully discussed. In this paper we review evidence supporting two thus far independently investigated mechanisms for this social bonding effect: self-other merging as a consequence of inter-personal synchrony, and the release of endorphins during exertive rhythmic activities including musical interaction. In general, self-other merging has been experimentally investigated using dyads, which provide limited insight into large-scale musical activities. Given that music can provide an external rhythmic framework that facilitates synchrony, explanations of social bonding during group musical activities should include reference to endorphins, which are released during synchronised exertive movements. Endorphins (and the Endogenous Opioid System (EOS) in general) are involved in social bonding across primate species, and are associated with a number of human social behaviours (e.g. laughter, synchronised sports), as well as musical activities (e.g. singing and dancing). Furthermore, passively listening to music engages the EOS, so here we suggest that both self-other merging and the EOS are important in the social bonding effects of music. In order to investigate possible interactions between these two mechanisms, future experiments should recreate ecologically valid examples of musical activities.